Expert IELTS 6 - Warwick, Clare Walsh Lindsay (Pearson, 2017)
This major new work by Professor Newmark is a textbook and a handbook of translation for English and foreign students working alone or on courses at degree and post-graduate level. Part one consists of a comprehensive discussion of most subjects and problems that arise in translating: the process of translating, text analysis, translation methods, text as a translation unit, translation procedures, cultural aspects of translation, use of case grammar and componential analysis, and the translation of metaphors. There are chapters on translation criticism and technical and literary translation, as well as revision, deadlines
Keywords: Expert; IELTS